Dietary Alpha-Lipoic Acid Alters Piglet Neurodevelopment - Mudd, Austin T.; Waworuntu, Rosaline V.; Berg, Brian M.; Dilger, Ryan N. (Frontiers in Pediatrics, 2016)
Introduction: Alpha-lipoic acid (a-LA) is an antioxidant shown to ameliorate age-associated impairments of brain and cardiovascular function. Human milk is known to have high antioxidant capacity, however the role of antioxidants in the developing brain is largely uncharacterized. This exploratory study aimed to examine the dose response effects of a-LA on piglet growth and neurodevelopment. Methods: Beginning at 2 d of age, 31 male pigs received one of three diets: control (CONT) [0 mg a-LA/100g], low a-LA (LOW) [120 mg a-LA/100g], or high a-LA (HIGH) [240 mg a-LA/100g]. From 14 to 28 d of age, pigs were subjected to spatial T-maze assessment and macrostructural and microstructural neuroimaging procedures were performed at 31 d of age. Results: No differences due to diet were observed for bodyweight gain or intestinal weight and length. Spatial T-maze assessment did not reveal learning differences due to diet in proportion of correct choices or latency to choice measures. Diffusion tensor imaging revealed decreased (P = 0.01) fractional anisotropy (FA) in the internal capsule of HIGH fed pigs compared with both the CONT (P < 0.01) and LOW (P = 0.03) fed pigs, which were not different from one another. Analysis of axial diffusivity (AD) within the internal capsule revealed a main effect of diet (P < 0.01) in which HIGH fed piglets exhibited smaller (P < 0.01) rates of diffusion compared with CONT piglets, but HIGH fed piglets were not different (P = 0.12) than LOW fed piglets. Tract-based spatial statistics, a comparison of FA values along white matter tracts, revealed 1,650 voxels where CONT piglets exhibited higher (P < 0.05) values compared with HIGH fed piglets. Conclusion: The lack of differences in intestinal and bodyweight measures among piglets indicate a-LA supplementation does not impact overall growth, regardless of concentration. Additionally, no observed differences between CONT and LOW fed piglets in behavior and neuroimaging measures indicate a low concentration of a-LA does not affect normal brain development. Supplementation of a-LA at a high concentration appeared to alter white matter maturation in the internal capsule, which may indicate delayed neurodevelopment in these piglets.